The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jfbc.13437
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid composition and antioxidant properties of the enzymatic hydrolysate of calabash nutmeg ( Monodora myristica ) and its membrane ultrafiltration peptide fractions

Abstract: The aim of this work was to determine amino acid composition and in vitro antioxidant activities of Monodora myristica protein hydrolysate and its membrane ultrafiltration peptide fractions. The Alcalase hydrolysate was fractionated using ultrafiltration membranes to produce peptide sizes of <1, 1-3, 3-5, and 5-10 kDa. The results showed that sequential fractionation resulted in higher glycine and glutamic acid and glutamine contents. Analysis of in vitro antioxidant properties showed that fractionation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…The amino acid composition of protein hydrolysates and peptides has been closely correlated with their antioxidant activity ( 51 ). It is reported that protein hydrolysates and/or peptides containing amino acid residues such as valine (Val), alanine (Ala), leucine (Leu), phenylalanine (Phe), tryptophan (Trp), methionine (Met), aspartic acid (Asp), proline (Pro), and histidine (His) show higher antioxidant ability ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid composition of protein hydrolysates and peptides has been closely correlated with their antioxidant activity ( 51 ). It is reported that protein hydrolysates and/or peptides containing amino acid residues such as valine (Val), alanine (Ala), leucine (Leu), phenylalanine (Phe), tryptophan (Trp), methionine (Met), aspartic acid (Asp), proline (Pro), and histidine (His) show higher antioxidant ability ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it shows activity in the OH radical scavenging experiment in this paper. Moreover, according to Piu et al ( 53 ) and Akinyede et al ( 51 ), acidic or basic amino acids, like Asp, Glu, Arg, and the presence of His residue containing imidazole ring, which was responsible for metal chelation through enhancing electrostatic and ionic interactions with iron. In summary, the presence of these amino acids makes A-BRPH could, to some extent, exert different antioxidant properties in different oxidative systems.…”
Section: Resultsmentioning
confidence: 99%
“…Cit has the characteristics of a hydroxyl radical scavenger [ 51 ]. Glutamic acid and histidine decreased the generation of the hydroxyl radicals [ 52 ]. Hwang et al demonstrated a strong antioxidant activity of methionine and lysine [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, SHP2 was significantly stronger than SHP4 and SHP5 at the same concentration, but lower than GSH. In biological systems, antioxidants inhibit the continuous oxidation reactions as reducing reagents, and the capacity is positively related to their antioxidant activity [48]. The result showed that SHP2 can be used to reduce the oxidation intermediates in the lipid peroxidation reaction of organisms as reducing reagents.…”
Section: Reducing Powermentioning
confidence: 99%
“…Furthermore, the component and sequences of amino acids were also important factors that could affect antioxidant activity. Some hydrophobic amino acids, such as methionine (Met), tryptophan (Trp), valine (Val), proline (Pro), alanine (Ala), leucine (Leu) or phenylalanine (Phe), can play a significant role in antioxidant peptides [48,54], through increasing the solubility of peptides in lipids and enhancing the interaction with oxidant substances. Ketnawa et al [55] believed that if the peptides contain high proportions of aromatic amino acids (His, Trp) or Leu, Ala and Pro, they could directly transfer electrons, and hence they are always linked to strong antioxidant activity.…”
Section: The Relationship Between Structure and Activitymentioning
confidence: 99%